If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x-2(x-10)=02(4x)-7
We move all terms to the left:
3x-2(x-10)-(02(4x)-7)=0
We multiply parentheses
3x-2x-(024x-7)+20=0
We get rid of parentheses
3x-2x-024x+7+20=0
We add all the numbers together, and all the variables
-23x+27=0
We move all terms containing x to the left, all other terms to the right
-23x=-27
x=-27/-23
x=1+4/23
| b/7+47=56 | | -w+4=(3w-13)=0 | | w+4=(3w-13)=0 | | 20=w-69 | | 3x^2+3x-110=0 | | 11x^2-49x-30=0 | | 3x^2+3x-130=0 | | 3x^2+3x-170=0 | | 5=w-16 | | 3x^2+3x-120=0 | | 3x^2+3x-150=0 | | 5=w-69/4 | | 2x–x=31 | | 4h-1=2 | | 6n-20+5n+11=180 | | 5(k-7)-k+7=0 | | 2x^2+2x-170=0 | | 19=4p+7 | | 2x^2+2x-130=0 | | 2x^2+2x-120=0 | | 3(2y+5y)=0 | | |5x+8|=|4x+10| | | 6+-12+2=v | | -4(x+3)=-5(x-1)+3x+2 | | 6+-12+2=a | | 17+2/11+171-x=180 | | 11x=189 | | 6x-20+5x+11=180 | | 14z-1264+1,494°z=95 | | a+3a+7=37 | | x^2+x-175=0 | | 201=114-x |